Anticipatory action simulation on flood hazard: case study of Matara District, Sri Lanka - Alahacoon, Niranga; Amarasinghe, H.; Indrasena, R.; Gunasundara, W.; Kaushalya, C.; Nethmi, K.; De Silva, R.; Amarnath, Giriraj (International Water Management Institute, 2025)
A large-scale community flood simulation exercise was carried out on 15–16 September 2025 in the Wellathota and Katuwangoda GN Divisions of the Matara District, Sri Lanka—areas highly vulnerable to recurrent flooding. The exercise aimed to enhance community preparedness by testing the early warning dissemination process, validating early action protocols, and assessing the capacity of Village Disaster Management Committees (VDMCs). Led by the District Disaster Management Coordination Unit under the guidance of the Disaster Management Centre (DMC) and supported by Save the Children International (SCI), the International Water Management Institute (IWMI), and the Sahana Social Development Alliance (SSDA), the simulation followed the structured Preparedness, Readiness, and Active phases of Anticipatory Action. Communities practised vital preparedness and readiness actions such as canal cleaning, early harvesting, securing essential items, preparing go-bags, checking rescue boats, installing indicator poles, and safeguarding livestock. During the Active Phase, actions included mock cash assistance, first-aid demonstrations, focused support for vulnerable groups, and establishing safe spaces for children. Evacuation drills were conducted efficiently, with families relocating to shelters and engaging in camp management activities coordinated by disaster management officials and Family Health Officers. After the “all clear” signal, families returned home, cleaned the shelters, and participated in a reflection session to identify strengths, gaps, and lessons for improving future flood preparedness.